2016 IEEE International Geoscience and Remote Sensing Symposium (IGARSS) 2016
DOI: 10.1109/igarss.2016.7730271
|View full text |Cite
|
Sign up to set email alerts
|

Detection of sea ice based on BeiDou-reflected signals

Abstract: For preventing the effects of sea ice bring the serious negative impact on the maritime transport, a full-scale detection of sea ice should be performed. The BeiDou GEO satellites could provide stable geometry and better coverage in mid-and low-latitude region where most of the sea ice occur. Based on this consideration, this paper evaluates the usage of BeiDou GEO Satellites reflected signals for accurate real-time Earth observation to study the changes in the sea surface state through remote sensing. BeiDou … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…Han et al [19] proposed a method for sea ice image classification based on heterogeneous data fusion and deep learning, effectively fusing SAR and optical imagery to enhance the precision of remote sensing sea ice classification. Gao et al [20] evaluated accurate observations of remote sensing sea ice using reflected signals from the BeiDou Geostationary Earth Orbit (GEO) satellite. Gao et al [21] introduced a convolutional-wavelet neural network-based approach for sea ice change detection, mitigating the influence of inherent speckle noise in multi-temporal SAR images.…”
Section: Introductionmentioning
confidence: 99%
“…Han et al [19] proposed a method for sea ice image classification based on heterogeneous data fusion and deep learning, effectively fusing SAR and optical imagery to enhance the precision of remote sensing sea ice classification. Gao et al [20] evaluated accurate observations of remote sensing sea ice using reflected signals from the BeiDou Geostationary Earth Orbit (GEO) satellite. Gao et al [21] introduced a convolutional-wavelet neural network-based approach for sea ice change detection, mitigating the influence of inherent speckle noise in multi-temporal SAR images.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the concentration of sea ice is correlated with the polarization ratio of BeiDou GEO satellites [24]. The same application was also tested in [25]. The soil moisture retrieval method was proposed based on the reflected signals from BeiDou GEO satellites, using a support vector regression machine (SVRM)-assisted method.…”
Section: Introductionmentioning
confidence: 99%